Ethnobotany in science education: A pathway for biology teachers to engage with climate change and local knowledge - Melo Gomes, Fernanda; Souza Lobo dos Santos, Marina Sunshine; Lacerda Ramos, Luiza Olívia; Diele Viegas, Luisa Maria (Ethnobotany Research and Applications, 2026)
Background: Ethnobotany is an essential science for biocultural conservation and climate resilience, helping explain human-plant relationships in socio-ecological contexts. However, integrating Local Ecological Knowledge (LEK) and climate change into science education remains challenging in schools serving traditional and socially vulnerable communities, due to curricular rigidity, limited resources, and disconnection between curricula and local realities. This study investigates how Brazilian Biology teachers navigate these barriers in their pedagogical practices. Methods: Using mixed methods, we conducted semi-structured questionnaires and interviews with Biology teachers from eight public schools across Brazil’s North, Northeast, and South regions, selected for socio-environmental vulnerability and proximity to traditional communities. Analysis included thematic coding, descriptive statistics, Spearman’s correlations (ethnobotany inclusion × teacher self-efficacy), and Fisher’s exact test for regional Didactic Sequences (DS) adoption patterns. Results: While 92% of teachers acknowledge ethnobotany’s relevance, implementation revealed structural gaps. Curricula prioritized curriculum-based botanical content (morphology: 64%; reproduction: 55%) over LEK-related themes (medicinal plants: 36%; Unconventional Food Plants: 27%). Climate change education relied predominantly on expository methods (78%), with place-based strategies being marginal. DS adoption was low, with no significant regional association (p = 0.776). Three barriers were identified: 1) disconnection between curricula and community knowledge, 2) lack of contextualized materials, and 3) structural constraints in teacher training. Conclusions: Despite barriers, pedagogical resilience emerged through school gardens, community-based projects, and locally adapted DS. We recommend co-developing materials with communities strengthening teacher training through intercultural and place-based approaches and building collaborative networks between schools and universities to embed ethnobotany and climate justice within science curricula. Keywords: Brazil; Biology teaching; Climate crisis; Local Ecological Knowledge, Vulnerable communities